Limitation on human rights in Vietnam: constitutional implications and enforcement perspective - Le, Quynh Mai (Đại học Quốc gia Hà Nội, 2020)
The 2013 Constitution for the first time stipulates the principle of limitation on human rights: “Human rights and citizens’ rights can only be limited in accordance with the law in case of necessity for reasons of national defense, national security, order, and social security, social ethics, public health” (Clause 2, Article 14). This constitutional recognition ensures that human rights cannot be arbitrarily restricted by public authorities. This constitutional principle and other amendments of the 2013 Constitution on human rights are among the most progressive provisions of the 2013 Constitution, contributing to making the Vietnamese Constitution closer to constitutionalism and international law. Although state agencies, especially the National Assembly, have had certain positive changes in referring and using the principle of limitation in the making of laws and regulations, the enforcement of the principle has not yet been enforced fully in practice. One of the main causes of this problem is the absence of an effective constitutional protection mechanism. This article will examine the principle of limitation in the 2013 Constitution. It also analyzes the problems of the implementation of the 2013 Constitution. This article will evaluate the principle of human rights limitation in the 2013 Constitution. In addition to analyzing the significance of the constitutional recognition of human rights limitation, this comparative and current legal provisions analysis will allow us to answer the question if it has brought positive practical changes in rights protection in Vietnam. The article then concludes that the constitutional principle of limitation cannot be implemented due to the lack of an effective constitutional mechanism.